2014
DOI: 10.5194/acpd-14-14725-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detailed source term estimation of the atmospheric release for the Fukushima Daiichi Nuclear Power Station accident by coupling simulations of atmospheric dispersion model with improved deposition scheme and oceanic dispersion model

Abstract: Abstract. Temporal variations in the amount of radionuclides released into the atmosphere during the Fukushima Dai-ichi Nuclear Power Station (FNPS1) accident and their atmospheric and marine dispersion are essential to evaluate the environmental impacts and resultant radiological doses to the public. In this paper, we estimate a detailed time trend of atmospheric releases during the accident by combining environmental monitoring data with atmospheric model simulations from WSPEEDI-II (Worldwide version of Sys… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
105
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(111 citation statements)
references
References 108 publications
6
105
0
Order By: Relevance
“…We have considered 131 I aerosol emission rates ( Fig. 1) given by Katata et al (2015) in the present simulation with a characteristic size distribution as shown in Table 1. The aerosol size distribution is lognormal with 0.4 µm as mode diameter and Geometric Standard Deviation (GSD) of 1.3 (Baklanov and Sorensen, 2001).…”
Section: Iodine-131mentioning
confidence: 99%
See 3 more Smart Citations
“…We have considered 131 I aerosol emission rates ( Fig. 1) given by Katata et al (2015) in the present simulation with a characteristic size distribution as shown in Table 1. The aerosol size distribution is lognormal with 0.4 µm as mode diameter and Geometric Standard Deviation (GSD) of 1.3 (Baklanov and Sorensen, 2001).…”
Section: Iodine-131mentioning
confidence: 99%
“…Various researchers have estimated its source term during FDNPP accident using inverse estimation methods (Stohl et al, 2012;Terada et al, 2012;Oza et al, 2013;Katata et al, (Katata et al, 2015). Cs emission rate (Katata et al, 2015) as shown in Fig. 1 with a lognormal size distribution (mode -1 μm and GSD -1.3) is considered (Baklanov and Sorensen, 2001).…”
Section: Caesium-137mentioning
confidence: 99%
See 2 more Smart Citations
“…A few years after this accident, we had slightly understood some findings regarding all the radioactivity for released radioactive cesium isotopes of Cs-134 and Cs-137 into the environment and the exact migrations for the radioactive plumes including those radioactive materials upon atmospheric conditions [1][2][3][4][5]. Four years elapsed and it has now become clear that the radioactive materials have chemical and physical properties concerning chemical forms, particle sizes, shape, phases (gas or aerosol), water solubility, and residence time [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%